How Much Compensation Can CEOs Permissibly Accept? - Moriarty, Jeffrey (Business ethics quarterly, 2009)
Debates about the ethics of executive compensation are dominated by familiar themes. Many writers consider whether the amount of pay CEOs receive is too large—relative to firm performance, foreign CEO pay, or employee pay. Many others consider whether the process by which CEOs are paid is compromised by weak or self-serving boards of directors. This paper examines the issue from a new perspective. I focus on the duties executives themselves have with respect to their own compensation. I argue that CEOs’ fiduciary duties place a moral limit on how much compensation they can accept, and hence seek in negotiation, from their firms. Accepting excessive compensation leaves the beneficiaries of their duties (e.g., shareholders) worse off, and thus is inconsistent with observing those duties.